Fertilizer producer makes Raton home - Williams, Curtis (Raton, NM Raton Range, 1996)
This article is about a new manufacturing business, International Humate Co., coming to the Raton area.
Newspaper article + Photograph of David Williams and J.D. Rottweiler
Master list item #: 58
File location is in the Raton file Cabinet
Keywords: Williams, David -- President of International Humate Co; Rottweiler, J. D. -- International Humate Co. Chief Financial Officer; Schmeits, Ron -- International Bank President; Honeyfield, Eric -- City Manager; Apache, Joe -- Raton Mayor; International Humate Co; Armex Plaza; Intrenational Bank; Raton Water Works; Raton Street Department; Leonardite; Fertilizer Products; Small Companies; Manufacturing; Raton, New Mexico